Using prefixes and suffixes as vocabulary learning strategies for Russian (Philology, 2024)
In the contents of Russian textbooks, prefixes are emphasized in sections regarding verbs of motion and verb aspects through prefixation; therefore, learners tend to overlook the importance of suffixes. In this regard, learners do not employ suffixes due to the lack of descriptions in the textbooks. Hence, this study examined the use of Russian derivational prefixes and suffixes as vocabulary learning strategies. For this purpose, the author administered a questionnaire to students majoring in Russian language as their first foreign language at the author’s university regarding the use of derivational prefixes and suffixes when learning Russian vocabulary. In comparison with the primary literature (Schmitt 1997), the data obtained from the questionnaire were analyzed using a mixed methods research approach. The findings showed that most learners used prefixes to discover the meanings of unknown words and consolidate them in their memory; however, they did not use suffixes for these purposes and did not consider them to be effective as vocabulary learning strategies. The results highlight the following two points: (1) in contrast to English learners, Russian learners do employ vocabulary learning strategies with prefixes and suffixes. (2) However, they have greater knowledge of prefixes than that of suffixes. For the first time, this study revealed the details about the use of Russian affixes as learning strategies. Since previous research has indicated that knowledge of suffixes is significant for increasing Russian vocabulary, Ru
Keywords: Russian vocabulary learning strategy; word-formation; prefixes; suffixes